2022
DOI: 10.1093/rheumatology/keac266
|View full text |Cite
|
Sign up to set email alerts
|

Worse outcomes linked to ethnicity for early inflammatory arthritis in England and Wales: a national cohort study

Abstract: Objective To assess variability in care quality and treatment outcomes across ethnicities in early inflammatory arthritis (EIA). Methods We conducted an observational cohort study in England and Wales from May 2018-March 2020, including patients with a suspected/confirmed EIA diagnosis. Care quality was assessed against six metrics defined by national guidelines. Clinical outcomes were measured using DAS28. Outcomes between e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…This directly contrasts with previous perceptions that some ethnic minority groups, such as South Asians developed less severe diseases with rheumatoid arthritis (RA). Adjustment for the social class has not changed the differences in outcomes [3]. There have been multiple other studies over the last decade in the UK demonstrating poorer outcomes in BAME patients [4,5].…”
mentioning
confidence: 94%
“…This directly contrasts with previous perceptions that some ethnic minority groups, such as South Asians developed less severe diseases with rheumatoid arthritis (RA). Adjustment for the social class has not changed the differences in outcomes [3]. There have been multiple other studies over the last decade in the UK demonstrating poorer outcomes in BAME patients [4,5].…”
mentioning
confidence: 94%
“…The participation of men and those from ethnic minority backgrounds remained low and these patients often have poorer outcomes (Adas et al., 2023). This is often the case with such surveys and work is being performed to understand and address this.…”
Section: Discussionmentioning
confidence: 99%
“…Other key findings showed that people did not feel their concerns were adequately addressed when engaging with a virtual consultation. Relatively few participants suggested that an increased length in the consultation time would be necessary, which is The participation of men and those from ethnic minority backgrounds remained low and these patients often have poorer outcomes (Adas et al, 2023). This is often the case with such surveys and work is being performed to understand and address this.…”
Section: Methods Of Referral To Rheumatology Number (%)mentioning
confidence: 99%
“…Meanwhile, there are well-documented ethnic and socio-economic disparities in clinical outcomes for RA (7)(8)(9), suggesting a lack of health equity along the patient pathway. There is evidence that ethnicity and socio-economic status influence the symptomatic presentation to primary care (8,10) and patients of non-White ethnicity and low socioeconomic status may be more likely to present with "atypical" musculoskeletal symptoms than their White or more affluent counterparts.…”
Section: Introductionmentioning
confidence: 99%